ANALYSIS OF THE IMPACT OWNERSHIP STRUCTURE AND FIRM SIZE ON CREDIT RISK OF PRIVATE BANKS PERIOD 2018-2022 - Muhammad Faisal; Meiske Wenno (Jurnal Ekonomi, 2023)
This study aims to investigate the impact of managerial and institutional ownership structure, as well as company size, on credit risk in national private banks in Indonesia during the period of 2018-2022. The population of this study is all national private banks, which amounts to 68 banks. The sample selection is done through purposive sampling, and 14 banks meet the criteria as the research sample. The data analysis method used in this research is panel data regression analysis using SPSS software. In conclusion, these findings suggest that the ownership structure of both managerial ownership and institutional ownership has a significant influence in playing an important role in shaping private bank credit risk, while the firm size does not have a significant impact on credit risk.. The study also highlights the importance of good corporate governance implementation in influencing bank risk management.